2013
DOI: 10.1590/s0102-05362013000400019
|View full text |Cite
|
Sign up to set email alerts
|

Absorção de nutrientes em cultivares de gérbera cultivada em vaso

Abstract: A análise da absorção de nutrientes ao longo do ciclo da cultura é importante para o conhecimento das necessidades nutricionais nas épocas de maior demanda e programar a fertirrigação, sendo escassas as informações para gérbera. Assim, o objetivo foi quantificar a absorção das cultivares de gérbera de vaso Cherry e Red, conduzidas em substrato em um ciclo de cultivo no período de agosto a outubro de 2008. O experimento foi realizado em casa-de-vegetação com delineamento em blocos ao acaso, com parcela subdivid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…From 180 to 360 day of cultivation in pot there was a four-fold increase in nutrient accumulation. Nutrient uptake increases during the reproductive stage of potted gerbera was also observed by Ludwig et al (2008); Guerrero et al (2012) and Ludwig et al (2013). At 360 day of cultivation, the accumulation followed the decreasing order: K > Ca > N > Mg > P > S (1059; 652; 515; 305; 171; and 148 mg per plant), while for micronutrients Mn > Fe > Zn > B > Cu (20.7; 14.9; 3.7; 1.4; and 0.6 mg per plant).…”
Section: Resultsmentioning
confidence: 53%
“…From 180 to 360 day of cultivation in pot there was a four-fold increase in nutrient accumulation. Nutrient uptake increases during the reproductive stage of potted gerbera was also observed by Ludwig et al (2008); Guerrero et al (2012) and Ludwig et al (2013). At 360 day of cultivation, the accumulation followed the decreasing order: K > Ca > N > Mg > P > S (1059; 652; 515; 305; 171; and 148 mg per plant), while for micronutrients Mn > Fe > Zn > B > Cu (20.7; 14.9; 3.7; 1.4; and 0.6 mg per plant).…”
Section: Resultsmentioning
confidence: 53%
“…Different nutrient demands by cultivars of the same species were observed by Villas Bôas et al (2008) in rose, by Ludwig et al (2013) in gerbera and by Ferreira et al (2012) in chrysanthemum. According to Horn et al (2006) and Rengel & Damon (2008), this difference is due to genetic characteristics and is caused by the variation in the kinetic parameters of nutrient uptake and morphological differences of the root system.…”
Section: Traitmentioning
confidence: 75%
“…Santos et al (2017) observed that organic fertilization with industrial waste did not increase shoot and inflorescence diameters of potted gerbera, in relation to mineral fertilization. Ludwig et al (2013) found that P was the fifth macronutrient most required by the Red potted gerbera, and the accumulated amount of nutrient in the plant shoot was 42 mg plant -1 . According to the authors, this value was 12.5; 8.0; and 2.8 times lower than the accumulated amounts of K, N, and Ca by plants.…”
Section: Resultsmentioning
confidence: 95%